2009
DOI: 10.3855/jidc.240
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem resistance in Acinetobacter baumannii: the molecular epidemic features of an emerging problem in health care facilities

Abstract: Acinetobacter baumannii is an opportunistic gram-negative pathogen with increasing relevance in a variety of nosocomial infections especially among intensive-care-unit (ICU) patients. Carbapenems have been widely used to treat serious multidrug-resistant A. baumannii infections; however, incidences of carbapenem-resistant A. baumannii are rising in several parts of the world and large and sustained outbreaks caused by such bacteria have been described. Carbapenem-resistant A. baumannii epidemics are sustained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
125
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 52 publications
(130 reference statements)
2
125
0
10
Order By: Relevance
“…OXA-type b-lactamases are responsible for the most common type of carbapenem resistance via enzymatic degradation (Zarrilli et al, 2009). Although MBLs are not the predominant carbapenemases in A. baumannii, VIM, IMP, SIM and NDM metallo-b-lactamases have been found to contribute to the high-level resistance to carbapenems (Lin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…OXA-type b-lactamases are responsible for the most common type of carbapenem resistance via enzymatic degradation (Zarrilli et al, 2009). Although MBLs are not the predominant carbapenemases in A. baumannii, VIM, IMP, SIM and NDM metallo-b-lactamases have been found to contribute to the high-level resistance to carbapenems (Lin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the same manner, piperacillin-tazobactam, ampicillin-sulbactam and amikacin were the most active drug after carbapenem, study results similar to report from Iran, Feizabadi et al (2008) found that 42.1 and 38.2% of carbapenem resistant A. baumannii were susceptible to piperacillin-tazobactam and amikacin, respectively. These findings suggest the presence of another resistance mechanism that has not been previously investigated, such as extended spectrum β-lactamases, the modification of penicillin-binding proteins and the up-regulation of the efflux system (Zarrilli et al, 2009).…”
Section: Discussionmentioning
confidence: 61%
“…They showed multiple epidemic strains that persisted two years in some cases in the two hospitals study. The analysis of the molecular epidemiology and multidrug resistance of A. baumanni strains in the various parts of the world indicates a considerable degree of geographic diversity in the spread of various strains [23,24,25,26]. It's also demonstrated by multiple studies in Tunisia [20,21,27] and in France [28,29,30] that the multiresistance is common among A.baumannii giving nosocomial epidemics which were difficult to treat.…”
Section: Discussionmentioning
confidence: 99%